2010
DOI: 10.1007/s12975-010-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Short Period of Early Reperfusion Aggravates Blood–Brain Barrier Dysfunction During Permanent Focal Ischemia in Rats

Abstract: Unintentional reperfusion is considered a complication in various experimental models of focal brain ischemia. In the present study, we evaluated whether short intermittent reperfusion affects ischemic brain damage and blood-brain barrier (BBB) integrity in a model of permanent focal ischemia. Focal brain ischemia was induced in male Sprague-Dawley rats using the filament method. A 20-s reperfusion period was allowed 0.5, 2, or 10 min after thread occlusion of the middle cerebral artery. In control animals, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The restrictive nature of the BBB is specifically due to tight junctions between adjacent endothelial cells, specifically occludin and ZO-1 . It has been reported that there is a direct correlation between the levels of tight junction proteins and the extent of endothelial barrier permeability, and the discontinuous appearances of tight junctions on the cell periphery provide a further explanation for the compromised BBB after cerebral ischemia. , Therefore, we next explored the role of BHDPC in MCAO-induced changes in tight junction protein characteristics, including expression and localization. First, as shown in Figures E and F, levels of both ZO-1 and occludin were significantly reduced in the MCAO brains (both p < 0.01 versus the sham group).…”
Section: Resultsmentioning
confidence: 99%
“…The restrictive nature of the BBB is specifically due to tight junctions between adjacent endothelial cells, specifically occludin and ZO-1 . It has been reported that there is a direct correlation between the levels of tight junction proteins and the extent of endothelial barrier permeability, and the discontinuous appearances of tight junctions on the cell periphery provide a further explanation for the compromised BBB after cerebral ischemia. , Therefore, we next explored the role of BHDPC in MCAO-induced changes in tight junction protein characteristics, including expression and localization. First, as shown in Figures E and F, levels of both ZO-1 and occludin were significantly reduced in the MCAO brains (both p < 0.01 versus the sham group).…”
Section: Resultsmentioning
confidence: 99%
“…Our data are in agreement with these studies demonstrating the generation of epileptiform activity due to thrombin application in the blood plasma media. Recent findings suggest a significant increase in the thrombin level in the brain tissue caused by the enhancement of BBB permeability during pathological conditions (Woitzik et al, 2011 ; Isaev et al, 2015 ). Thrombin, through its major receptor in the neural tissue, protease-activated receptors 1 (PAR 1), produces epileptogenesis by the escalation of brain damage, induction of seizures, inflammation, and neurogenesis (Rohatgi et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The suture was advanced with special care not to enter the pterygopalatine artery until an abrupt drop of the LDF signal indicated MCA occlusion. The suture was fixed to avoid shifting (Woitzik et al, 2011 ) and the neck incision was closed. After removing the LDF fibers from the skull anesthesia was discontinued and the animals were allowed to recover.…”
Section: Methodsmentioning
confidence: 99%